Prevalence of ECGs Exceeding Thresholds for ST‐Segment–Elevation Myocardial Infarction in Apparently Healthy Individuals: The Role of Ethnicity - ter Haar, C. Cato; Kors, Jan A.; Peters, Ron J. G.; Tanck, Michael W. T.; Snijder, Marieke B.; Maan, Arie C.; Swenne, Cees A.; van den Born, Bert‐Jan H.; de Jong, Jonas S. S. G.; Macfarlane, Peter W.; Postema, Pieter G. (Journal of the American Heart Association, 2020)
Background Early prehospital recognition of critical conditions such as ST-segment-elevation myocardial infarction (STEMI) has prognostic relevance. Current international electrocardiographic STEMI thresholds are predominantly based on individuals of Western European descent. However, because of ethnic electrocardiographic variability both in health and disease, there is a need to reevaluate diagnostic ST-segment elevation thresholds for different populations. We hypothesized that fulfillment of ST-segment elevation thresholds of STEMI criteria (STE-ECGs) in apparently healthy individuals is ethnicity dependent. Methods and Results HELIUS (Healthy Life in an Urban Setting) is a multiethnic cohort study including 10 783 apparently healthy subjects of 6 different ethnicities (African Surinamese, Dutch, Ghanaian, Moroccan, South Asian Surinamese, and Turkish). Prevalence of STE-ECGs across ethnicities, sexes, and age groups was assessed with respect to the 2 international STEMI thresholds: sex and age specific versus sex specific. Mean prevalence of STE-ECGs was 2.8% to 3.4% (age/sex-specific and sex-specific thresholds, respectively), although with large ethnicity-dependent variability. Prevalences in Western European Dutch were 2.3% to 3.0%, but excessively higher in young (<40 years) Ghanaian males (21.7%-27.5%) and lowest in older (≥40 years) Turkish females (0.0%). Ethnicity (sub-Saharan African origin) and other variables (eg, younger age, male sex, high QRS voltages, or anterolateral early repolarization pattern) were positively associated with STE-ECG occurrence, resulting in subgroups with >45% STE-ECGs. Conclusions The accuracy of diagnostic tests partly relies on background prevalence in healthy individuals. In apparently healthy subjects, there is a highly variable ethnicity-dependent prevalence of ECGs with ST-segment elevations exceeding STEMI thresholds. This has potential consequences for STEMI evaluations in individuals who are not of Western European descent, putatively resulting in adverse outcomes with both over- and underdiagnosis of STEMI.